Risk of postacute sequelae of COVID-19 and oral antivirals in adults aged over 60 years: A nationwide retrospective cohort study - Hyejin Joo; Eunji Kim; Kyungmin Huh; Gi Hwan Bae; Hyungmin Lee; Jungyeon Kim; Dong-Hwi Kim; Min-Gyu Yoo; Il Uk Jo; Poong Hoon Lee; Geun Woo Lee; Hee Sun Jung; et al. (International Journal of Infectious Diseases)
Objectives: To investigate the association between oral antiviral administration and postacute sequelae of COVID-19 (PASC) risk in Korea. Methods: This retrospective cohort study used data from the Korea Disease Control and Prevention Agency and the Health Insurance Review and Assessment Service. We analyzed data from COVID-19 patients aged >60 years from January to December 2022. The primary outcome was the occurrence of 27 PASCs within 30-120 days after COVID-19 diagnosis. The hazard ratio was calculated using the Cox proportional hazards model. Results: Nirmatrelvir/ritonavir significantly reduced the risk of cardiovascular diseases, including heart failure and cardiomyopathies (adjusted hazard ratio [aHR], 0.86), cardiac dysrhythmias (aHR, 0.83), and ischemic stroke (aHR, 0.88). Moreover, it also lowered the risk of hospitalization due to respiratory diseases including chronic obstructive pulmonary disease (aHR, 0.92), and decreased renal disorders including dialysis needs (aHR, 0.57), and acute renal failure (aHR, 0.85). Molnupiravir reduced the risk of ischemic stroke (aHR, 0.84) and other cerebrovascular diseases (aHR, 0.84). Respiratory conditions decreased by approximately 13-14% (aHR, 0.87 and 0.86, respectively). Conclusions: Nirmatrelvir/ritonavir and molnupiravir administration in ambulatory patients were associated with decreased PASC risk; thus, oral antivirals may mitigate the indirect Severe acute respiratory syndrome coronavirus 2 infection effects.